The influence of particle activated carbon on heavy metal passivation and antibiotic degradation in various organic fertilizers - Chi, Zifang; Li, Yuru; Li, Huai (Frontiers in Microbiology, 2025)
This study investigated the effects of different particle sizes of activated carbon [small particle activated carbon (S-AC, 2–4 mm), medium particle activated carbon (M-AC, 3–6 mm), and large particle activated carbon (B-AC, 5–8 mm)] on the physicochemical properties of organic fertilizers (chicken manure, sheep manure, cow manure and pig manure), the passivation of heavy metals, and the degradation of antibiotics. The results showed that the addition of particle activated carbon could increase the pH value of organic fertilizers, reduce the cation exchange capacity (CEC) value, and its fragmentation led to an increase in organic matter in organic fertilizers, but had no significant effect on the electrical conductivity (EC) value. The small particle activated carbon (S-AC) had high mechanical strength (compressive strength 4.014 MPa), low loss rate, and high recovery rate, showing the best remediation performance. After adding S-AC, the removal rates of total copper (Cu) and zinc (Zn) in organic fertilizers reached 23.71–28.57% and 15.41–17.81% respectively, and the maximum passivation rates of exchangeable fraction Cu and Zn were 61.31 and 29.10%. At the same time, S-AC significantly promoted the degradation of antibiotics, with the degradation rates of tetracycline (TC) and ciprofloxacin (CIP) reaching 81.38–85.81% and 76.53–80.59% within 30 days.